Pengaruh Perceived Ease Of Use, Perceived Usefulness Terhadap Intention To Use Online Single Submission (OSS) Dengan Trust Sebagai Variabel Mediasi Di Kementrian Investasi / BKPM - Vidiel Tania Pratama (Jurnal Publikasi Ilmu Manajemen, 2023)
This research was conducted to test and analyze the Effect of Perceived Ease of Use and Perceived Usefulness on Intention To Use through Trust as an Intervening Variable on Online Single Submission (OSS) Users at the Ministry of Investment (BKPM). In this research process, the data analysis technique used is the Structure Equestion Modeling (SEM) analysis technique using SmartPLS statistical software version 3.0, using data from the Ministry of Investment / BKPM. Results of research on 180 on Online Single Submission (OSS) Users regarding the effect of Perceived Ease of Use and Perceived Usefulness on Intention To Use through Trust in Online Single submission (OSS) Users at the Ministry of Investment (BKPM) (1). Perceived Ease of Use has a positive and significant influence on Trust in Online Single submission (OSS) Users (2). Perceived Usefulness has a positive and significant influence on Trust in Online Single submission (OSS) Users, (3), Perceived Ease of Use has a very positive and significant influence on Intention To Use on Online Single submission (OSS) Users, (4), Perceived Usefulness has a positive and significant influence on Intention To Use on Online Single submission (OSS) Users, (5), Trust has a positive and significant influence on Intention To Use on Online Single submission (OSS) Users, (6), Perceived Ease of Use has a positive and significant influence on Intention To Use through variable mediation Trust in Online Single submission (OSS) Users, (7). Perceived Usefulness has a positive and significant influence on Intention To Use through variable mediation Trust in Online Single submission (OSS) Users.